The Impact of Transformational Leadership Head of School and Discipline of Work on Performance of Junior High School Teachers in The Region of Gorontalo City - Pakaya, Abd. Rahman; Ishak, Venny (Asia Pacific Journal of Management and Education (APJME), 2019)
This study aims: 1) to determine the effect of principals' transformational leadership on the performance of junior high school teachers in Gorontalo City Region, 2) to determine the effect of work discipline on the performance of junior high school teachers in Gorontalo City Region, and 3) to determine the influence of Principal's transformational leadership and discipline simultaneous work on the performance of junior high school teachers in Gorontalo City Region. In this study, researchers used a survey approach with quantitative methods. To get accurate data, the distribution of 30 primary respondents was determined by means of proportional random sampling. After the data collected, it was processed using SPSS version 20 program, and analyzed by multiple linear regression. The results showed that: 1) principal transformational leadership had a positive and significant effect on the performance of junior high school teachers in Gorontalo City, 2) work discipline had a positive and significant effect on the performance of junior high school teachers in Gorontalo City, 3) principal transformational leadership and work discipline simultaneously has a positive and significant effect on the performance of junior high school teachers in Gorontalo City Region. Keywords: School Headmaster’s Transformational Leadership, Work Discipline, and Teacher’s Work